The Effect of E-Government on Corruption-International Evidence - Sugiarti, Rita; Akbar, Lutfia Rizkyatul (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
This study aims to prove the relationship between E-Government (E-Gov) and Corruption. GONE Theory is a theory that underlies someone committing corruption. The population is all countries in the world. The study periods are 2012, 2014, 2016, 2018, 2020, and 2022. The samples are selected using purposive sampling. The final observation amounts to 1026 (Unbalanced Firm-Year) consisting of 174 countries. Simple linear regression analysis is used with Stata. The results find that E-Gov has a significant effect in reducing corruption. Then, each EGDI element is used as an independent variable for robustness testing and show that each element has a significant effect on corruption. The higher EGDI score, the higher CPI score. A higher CPI score means that the country is cleaner from corruption, and vice versa. The results of the study can be generalized, but for better results it is necessary to add elements of citizens’ perceptions of E-Gov and corruption. Further research also needs to add control variables to avoid bias in research results.